The antiproliferative effect of parkia speciosa hassk (petai) (seed and pod) on colon cancer (HT29), cervical cancer (HeLa), and liver cancer (HepG2) cell lines - Hee, Zhen Yin
Rainforest of Malaysia is home to medicinal plants which have potential benefits to line of medicine and pharmacological. Parkia speciosa Hassk (petai) is known as a traditional medicinal plant which grows as wild plant or cultivated. This study aims to assess the antiproliferative effect of ethanolic and aqueous extracts of Parkia speciosa Hassk (seed and pod) on colon cancer (HT29), cervical cancer (HeLa), liver cancer (HepG2) cell lines and normal cell line (mouse fibroblast, BalB/c3T3). Ground lyophilized seed and pod were extracted by ethanol and deionised water separately, through shaking in dark at 25°C for 24hr. The ethanolic extracts were evaporated to dryness at 50°C, whereas the aqueous extracts were filtered and freeze dried. All cell lines were seeded in 96-well microtitre plate at density of 1x10⁵ cells/ml in each well. Concentrations used in treatment of each extract were 100.00µg/ml, 50.00µg/ml, 25.00µg/ml, 12.50µg/ml, 6.25µg/ml, and 3.13µg/ml. After 72hr of incubation, MTT [3-(4-5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay was performed to determine antiproliferative effect and absorbance value at 570nm of treatment and control groups were obtained. IC₅₀ value was determined from dose response curve with percentage of cell viability versus concentration for each extract. Parkia speciosa Hassk (petai) extract from both parts (seed and pod) did not cytotoxic to colon cancer (HT29) cell lines as IC₅₀ was not detectable for both aqueous and ethanolic extract. For HeLa cell lines, only aqueous extract from petai seed showed moderate cytotoxic against this cell lines as lC₅₀ value was 51.85µg/ml, whereas this cell lines was less sensitive to other petai extracts (lC₅₀>80µg/ml). The HepG2 cell lines was also showed less sensitive to all petai extracts from seed and pod where ICs₅₀ also closed to 100µg/ml. On normal cell line (3T3), lC₅₀ value of aqueous petai seed was 72.54µg/ml; aqueous and ethanolic petai pod were 50.99µg/ml and 30.87µg/ml respectively. Parkia speciosa Hassk (petai) extract from both parts (seed and pod) have low cytotoxic effect on all cancer cell lines studied. Extract from pod also have cytotoxic effect on normal cells (373). Further study need to be done to confirm this finding.